MIKROENKAPSULASI MINYAK SAWIT MERAH DENGAN VARIASI SUHU PENGERINGAN DAN JENIS BAHAN PENYALUT DENGAN METODE FOAM-MAT DRYING - Nur Endah Saputri; Ngatirah Ngatirah (Universitas Tanjungpura, 2019)
This study aims to determine the heat drying and kind of coating material for microencapsulated by physicochemical and organoleptic properties. Experimental design use Divide Plot Design (DPD) with two variables. The various heat drying (S) namely 50°C (S1), 60°C (S2), dan 70°C (S3), while as a section plot is a kind of coating mateials namely Na-Alginate (L1), Starch (L2), Carboxyl Methy Cellulose (L3), dan Chitosan (L4). The result showed variations of heat drying did not affect physical, chemical, and preference (color and texture) tests. The kind of coating material influences, water content, oil content, solubility, and preference test (color & texture), but does not significantly affect the content of free fatty acids, peroxide numbers, and carotenoid levels. The best overall results were found in microencapsulates with Starch coating ingredients with properties: 2.08% water content, free fatty acid content 0.63%, peroxide number 23.61 meq / kg, carotenoid levels 131.61 ppm, levels oil encapsulated 53.62%, solubility 57.03%, and munshell 91 color (dark yellow).